EFFICACY AND SAFETY OF BISOPROLOL IN YOUNG MEN WITH ARTERIAL HYPERTENSION AND OBESITY - A. G. Avtandilov; I. I. Esenova; S. L. Petrosov (Столичная издательская компания, 2016)
Aim. To evaluate effect of bisoprolol on circadian blood pressure (BP) profile, autonomic cardiovascular regulation, lipid and carbohydrate metabolism in young patients with arterial hypertension (HT) and obesity. Materials and methods. 36 men aged 18 to 35 years with HT 1-2 degrees, obesity 1-2 degrees and signs of sympathetic over activity were examined. In addition to standard clinical examination assessment of heart rate variability (HRV) during orthostatic test with spectral analysis, ambulatory BP monitoring, evaluation of lipid profile, oral glucose tolerance test, determination of immunoreactive insulin, insulin resistance index and functional activity of beta-cells were performed. Anthropometric measurements included body mass index and waist circumference. Bisoprolol in the initial dose of 5 mg QD orally for 12 weeks was assigned to all patients. After 12 weeks of bisoprolol treatment repeated examination was performed. Results. Significant changes in HRV after 12 weeks of treatment with bisoprolol was found. Parasympathetic influence of autonomic nervous system increased during orthostatic test. Contribution of the slow and very slow waves, which reflect sympathetic and neurohumoral activity , reduced. Total spectral power was significantly increased. Initial tachycardia reduced. Target BP values were achieved after 12 weeks of treatment with bisoprolol 5 mg QD. Increase in a number of dippers and decrease in a number of nondippers in terms of both systolic and diastolic BP was observed. Heart rate and HRV was significantly decreased. No adverse events in terms of lipid or carbohydrate metabolism were found during treatment with bisoprolol. Conclusion. Bisoprolol 12 week treatment resulted in sympathetic activity decrease and parasympathetic activity increase, achievement of BP target levels, improvement of BP circadian profile. Bisoprolol therapy in dose of 5 mg/day demonstrated metabolic neutrality in patients with risk factors of cardiovascular diseases and type 2 diabetes.